Model Mediasi Work Engagement dalam Hubungan Job Crafting dan Organizational Citizenship Behavior pada Industri Manufaktur - Wiliansyah, Ilham; Pusparini, Desak Made Dhinda; Puspitasari, Gayatri; Aryaputra, Brahmana; Zhibin, Zhang (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to elaborate the psychological mechanisms underlying the relationship between job crafting and Organizational Citizenship Behavior (OCB) by positioning work engagement as a mediating variable, particularly within the context of labor-intensive manufacturing sectors. Using an explanatory quantitative design, a survey was conducted among 155 employees of PT X selected through convenience sampling. Data were collected using adapted versions of the Job Crafting Scale, OCB Scale, and the Utrecht Work Engagement Scale (UWES-17). Data analysis employing multiple regression and path analysis revealed empirical findings that job crafting contributes significantly to OCB, both directly and through the partial mediation of work engagement. These findings indicate that employees who proactively modify aspects of their jobs especially by seeking challenges tend to exhibit higher levels of absorption and dedication, which in turn stimulate voluntary behaviors that benefit organizational effectiveness. The study concludes that providing employees with controlled autonomy to engage in job crafting is a vital strategy for enhancing extra-role performance in industrial environments.